Properties and evaluation of functionalized mixed membrane adsorbents for the adsorption of vanillic acid from palm oil waste - Zaharah, Abdul Rahman; Nora’aini, Ali; Sofiah, Hamzah; Syed Mohd Saufi, Tuan Chik; Norhafiza Ilyana, Yatim; Siti Solihah, Rasdei; Jan, Setiawan (Semarak Ilmu Publishing, 2024)
Identifying factors that can improve the ability of mixed matrix membrane (MMM) adsorbents to isolate phenolic chemicals from palm oil waste is a major challenge. This study prepared a mixed matrix membrane with improved efficiency using a quaternary doping solution and a hydroxyapatite (HAp) filler and denoted as modified mixed matrix membrane (MMMHAp). Prior to use, HAp powder obtained from eggshells calcined at different temperatures was evaluated as an absorbent for the desired phenolic compounds. All the prepared HAp and MMMHAp powders were evaluated for their properties by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and X-ray diffraction (XRD). For this study, vanillic acid was selected as a phenolic chemical because it is widely used in the pharmaceutical, biomedical and food industries. The optimal adsorption and vanillic acid isolation from crude palm oil samples by MMMHAp occurred using an acetate buffer solution with a pH of 8. The data from the equilibrium adsorption study were also in agreement with the Freundlich isotherm, as the R2 value was 0.9900 suggesting heterogeneous adsorption of vanillic acid on the surface of MMMHAp. The kinetic adsorption study clearly shows a pseudo-second-order fit (R2=0.9992), suggesting that chemisorption occurs between the adsorbed substance and the adsorbent. The modified membrane (MMMHAp) has characteristics of its finger-like structures is more elongated and connected to the porous layer, indicating that the incorporation of hydroxyapatite nanoparticles into the membrane enhances the adsorption of vanillic acid from real sample and has the highest adsorption capacity of 170.8 mg/g. These results show that this improved MMMHAp can be developed and used for waste utilization to obtain useful materials.